The Influence of Digital Behavior and Professional Learning Community on the Professionalism of Elementary School Teachers in North Penajam Paser District - Harisah, Harisah; Karwanto, Karwanto; Trihantoyo, Syunu; Khamidi, Amrozi (Journal of English Language and Education, 2026)
A quantitative approach with a causal design was used in this study to analyze the influence of Digital Behavior and Professional Learning Community on the Professionalism of Elementary School Teachers in Penajam Paser Utara Regency in the 2025/2026 academic year. The independent variables were defined as Digital Behavior (X1) and Professional Learning Community (X2), while the dependent variable was defined as Teacher Professionalism (Y). The study population consisted of 520 public elementary school teachers spread across four sub-districts. The sample was determined using the Slovin formula at a 7% error rate, resulting in 147 respondents and then rounded to 150 teachers to increase accuracy. The sampling technique was proportional random sampling. Data were collected using a five-level Likert-scale closed questionnaire. All instruments were tested for validity and reliability before use. Data analysis was performed using SPSS version 22 through classical assumption tests (normality and linearity) and multiple linear regression. Hypothesis testing was carried out at a significance level of 0.05 and strengthened by the coefficient of determination (R²). The results of the study show that partially and simultaneously, Digital Behavior and Professional Learning Community have a positive and significant influence on Teacher Professionalism. These findings imply that strengthening teachers’ digital competencies and fostering collaborative professional learning communities within schools are essential strategies to enhance teacher professionalism and improve the quality of elementary education.